2015
DOI: 10.5505/tjtes.2015.54358
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effects of adalimumab on rats with experimental peripheral nerve injury: an electron microscopic and biochemical study.

Abstract: BACKGROUND: Adalimumab, a new-generation anti-inflammatory agent, exerts its effect through tumor necrosis factor α (TNF-α), secreted from immune response cells such as macrophages and lymphocytes. TNF-α has been shown to play an important role in the processes of apoptosis and demyelination, and blockage of its activity may improve neural healing. Investigated in the present study is the probable neuroprotective influence of adalimumab in rats using a peripheral nerve injury model with biochemical and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This dosage and treatment regimen was decided according to the literature. [6] The animals tolerated this dosage well without any important side effects.…”
Section: Groupsmentioning
confidence: 88%
“…This dosage and treatment regimen was decided according to the literature. [6] The animals tolerated this dosage well without any important side effects.…”
Section: Groupsmentioning
confidence: 88%
“…For predicting the candidate e cient treatment against SNI and the associated concurrent diseases, this study used DGIdb database for determining the therapeutic agents showing effects on reversing the abnormal up-regulation of SNI-associated hub genes. Tumor necrosis factor-alpha (TNF-α) is suggested to exert a vital part during demyelination and apoptosis, while blocking its expression enhances neural healing (54). According to previous reports, TNF-α antagonists are effective on Schwann cells and axons within SNI, and TNF-α is related to the modulation of axonal regeneration (55).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of epidemiological studies have suggested that, the anti-TNF-α therapies, including adalimumab, etanercept and adalimumab, are utilized to treat different peripheral nerve diseases, including chronic in ammatory demyelinating polyneuropathy, Miller Fisher syndrome, Guillain-Barré syndrome, mononeuropathy multiplex, multifocal motor neuropathy accompanied by conduction block, and axonal sensorimotor polyneuropathy (56). Adalimumab was detected as the e cient neuroprotective drug to heal the nerves in PNI model of rats, particularly in the early phase (54). Trastuzumab have also been reported to enhance peripheral nerve regeneration following repair from acute and chronic PNI (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose adalimumab (5 mg/kg/day) was observed to exhibit ameliorative effects on the intestinal injury induced through H/R in the present study, whereas the high dose of adalimumab (50 mg/kg/day) did not exhibit similar properties. Polat et al also showed that low-dose adalimumab (5 mg/kg) has beneficial effects on ischemia/reperfusion-induced peripheral nerve injury, whereas a high dose of adalimumab (50 mg/kg) had no similar effects [10]. In the previous studies with rats, adalimumab was used at different low doses such as 5 mg/kg and 10 mg/kg, and at a higher dose such as 50 mg/kg [9,10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies investigated the effectiveness of adalimumab at different doses. In those studies, adalimumab as an anti-inflammatory agent significantly decreased nerve tissue lipid peroxidation in rats with experimental peripheral nerve injury, and it had beneficial effects on experimentally induced acute pancreatitis in rats [9,10]. The current study aimed to determine dose-dependent effects of adalimumab on intestinal injury induced with H/R in neonatal rat pups.…”
Section: Introductionmentioning
confidence: 92%